The Peer-Reviewed Literature on Undergraduate Education for Public Health in the United States, 2004–2014 - Evashwick, Connie J.; Tao, Donghua; Arnold, Lauren D. (Frontiers in Public Health, 2014)
The education of undergraduate college students in the field of public health has burgeoned over the past decade. Professional literature in peer-reviewed journals is one indicator of the status of a field of study and its related body of knowledge. It is also a mechanism for sharing information among professionals about challenges, issues, experiences and best practices. The purpose of the literature review conducted here was to describe the status of the peer reviewed literature over the past decade pertaining to the education of undergraduates about the field of public health in the U.S. A literature search was conducted of three data bases: PubMed, Scopus and ERIC. Inclusion criteria were publication date from January 1, 2004 through July 31, 2014; written in the English language; pertaining to undergraduate education in the U.S.; and a focus on public health as the primary discipline. Public health was searched as an overarching discipline; articles focused on sub-disciplines or other health professions disciplines were excluded. The search resulted in 158 articles. Each of the authors reviewed the abstracts for all articles and read full articles when necessary. The result was 23 articles that were then considered in depth. The articles were categorized according to their primary theme: curriculum, courses, learning objectives (N=14); evaluation of teaching method (N=3); case study (N=3); career path and advising (N=2); accreditation (N=1). Year of publication and journal were also examined. The results of the literature search lead to several observations about how the peer reviewed literature has been used to date and how it could be used to advance the emerging field of undergraduate education for public health.